Innovation as a Company Strategy in Efforts to Achieve Business Success - Suharto , Suharto (SEAN Institute, 2023)
In an ever-changing global context, companies need to continually develop new approaches to remain competitive. This research aims to investigate the role of innovation as a company strategy in achieving business success. This research uses a qualitative approach with descriptive methods. The research results show that innovation as a company strategy has a positive impact on business success in the industry [specify type of industry]. The implementation of innovation, both in products and processes, is proven to provide competitive advantage by increasing operational efficiency, speeding up production cycles, and reducing waste. Companies that successfully implement innovation also achieve cost and product quality advantages, win customer trust, and build strong relationships. Therefore, the recommendation for companies in this industry is to continue to encourage a culture of innovation, invest in research and development, and maintain an open approach to new ideas in order to maintain competitiveness and achieve sustainable business success.